'New Life Sciences: The Road Ahead' Report on the BioVisionAlexandria 2016 Conference. (December 2016) - Elwakil, Marwa; Roman, Nathalie; Rassoul, Marwa Abdel; Elfayoumi, Israa; Sobeih, Yousra; El-Faham, Mohamed
The Bibliotheca Alexandrina (BA) has organised its eighth international biennial conference, BioVisionAlexandria (BVA) 2016 on 12–14 April 2016 in Alexandria, Egypt. The theme of BVA 2016 was 'New Life Sciences: The Road Ahead', where cutting-edge relevant research topics at the forefront of science were presented by a variety of world-wide renowned speakers. BVA 2016 hosted around 2000 participants and speakers of diverse backgrounds, creating a multi-disciplinary arena for dialogue to explore the opportunities, benefits, and controversial threats.